Pencegahan Penyebaran Virus Corona di Bandara Menggunakan Artificial Intellegence - Destivanesha Rina (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
Identifying the corona virus on international arrival passengers aims to find out whether the passenger has the corona virus or not. Corona virus is one of the health problems that really needs our attention now. Because this virus can cause death, and the way the virus is transmitted is very easy and fast. There are many things that can be done to reduce the spread of this virus to the territory of Indonesia, one of which is to identify the body temperature of each passenger on international arrivals at the airport. At the airport the identification of this virus is done by using Artificial Intelligence. One of the things that is the goal of developing artificial intelligence (AI) is to help humans. This often means imitating the abilities and intelligence of the person he is trying to help or replace. The tool used is the Thermal Scanner Camera that can see directly the body temperature of the passenger. And there are several kits that have been made to check directly whether there is a corona virus in the human body by using the Rapid Test and PCR Test. This research was conducted to see how important AI (artificial intelligence) is in helping reduce the spread of corona virus. According to some existing data, the use of Thermal Scanner Camera can help reduce the spread of corona virus at airports.